- Strategi Kantor Urusan Agama Dalam Upaya Penanganan Serta Pencegahan Terjadinya Pernikahan Dini (Di Bawah Umur) Di Kecamatan Abab - Agustin, Shintia; Darmawan, Candra (ScidacPlus, 2024)
This research is motivated by the existence of a problem, namely the problem of frequent divorce of underage marriages in recent years, in general the cause of divorce between young couples is 37.9% because of finances, 27.6% because of continuous quarrels, 17.2% because of interference. parents' hands, and 17.2% due to infidelity. Of course, this often becomes a problem because it violates the purpose of marriage itself for the peace of both. Marriage in the Koran is based on peace, love and affection between husband and wife. The aim of this research is to find out: (1) the factors that cause early marriage in Abab District and (2) the strategy of the Abab District KUA to overcome the impacts that occur due to underage marriage. This type of research is qualitative research. This research method is qualitative. The primary data source is five (05) religious instructors who work at the Abab District KUA office. Secondary data sources in this research are relevant books, journals and documents related to the problem being studied. Data collection uses observation, interviews and documentation. Data analysis uses qualitative analysis. The research results show that the factors that influence teenagers marrying early in Abab District are dropping out of school/not going to school, family financial conditions, mass media broadcasts, and unemployment. It was found that other influencing factors such as promiscuity, a free environment, and being away from religious teachings were found in low percentages. The Abab District KUA's strategy in preventing and overcoming the impacts of early marriage is to conduct outreach through religious lectures at wedding receptions, Friday sermons, and pre-marital guidance. The Adab District KUA mobilized religious extension officers to guide bridal couples through pre-marital guidance, family guidance, education and teaching activities as well as providing guidance to families marrying underage to avoid divorce.Keywords: Underage marriage, KUA Strategy, Divorce